The Effect of Self-Management Practices and Job Satisfaction on Work Loyalty of Telkomsel Orbit Employees in Bandung City - Didi Tarmidi; Rama Mustofa Urip Sentoso (Institute of Computer Science (IOCS), 2022)
Having loyal workers can provide many benefits for the company in addition to the low turnover of workers also gives the company an impetus to continue to grow. The study was conducted to test the influence of work loyalty through the variables of self-management practices and job satisfaction at the Telkomsel Orbit Office in Bandung City. A total of 134 questionnaires were distributed to selected respondents and used as a static analysis. The results of the calculation of multiple linear regression analysis showed that self-management practices and job satisfaction had a sufficient influence on Worker Loyalty by 32.5%. The observation of the results of the questionnaire calculation shows that the variable of job satisfaction has a greater point than self-management practice.